4.3 Selections of DNA-Encoded Libraries to Protein Targets on Living Cells - Cai,B.; Krusemark,C. J. (DNA-Encoded Libraries, 2024)
Membrane proteins play a crucial role in numerous physiological processes and are the most common targets of approved drugs. However, the difficulty in purifying membrane proteins has limited the application of DNA-encoded libraries (DELs) for these targets in drug discovery campaigns. In this chapter, two methodologies for the selection of DELs against cell-surface proteins directly on live cells are presented. The first method employs covalent crosslinking to capture transient interactions between DNA-linked ligands and membrane proteins, facilitating the removal of non-crosslinked molecules through stringent washing. The second approach utilizes an engineered biotin ligase enzyme tag on the target to selectively biotinylate DNA-linked ligands through induced proximity. These methods successfully address challenges such as low target-protein concentration on live cells and the low efficiency in purifying DNA–membrane-protein conjugates, offering promising tools for small-molecule discovery targeting membrane proteins.
Keywords: Referencework; DNA-encoded libraries; membrane proteins; crosslinking; biotin ligase; drug discovery; enzymatic turnover; selections